موقف الرسول الخاتم صلى الله عليه وسلم في توطيد الأمن والسلام - Mostafa Kamil Al-Madani (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024